The EDUCATION IN NAZI GERMANY FROM 1933 TO 1945 (Heritage, 2021)
This paper studies education during the Nazi Germany period, from 1933 to 1945. In order to achieve their goals, the Nazis who founded the National Socialist German Workers' Party (NSGWP), in addition to numerous laws and state programs, saw great importance in educational activities. The concretization of the goal of education during the period of Nazi Germany implied the education of children and youth on eugenics, nationalist, racist, anti-Semitic, ideological, occult, theosophical, militaristic and alchemical bases with the aim of encouraging and developing awareness of the importance and preservationof the pure Aryan race, about the German people as the most civilized and God-given to rule the world, with their sublime tradition and culture.
Keywords: Nazism, Third Reich, Aryan race, educational activities, eugenics, ideology, occultism, racism, fascism, anti-Semitism